Transformation of Student Leadership: Adopting Entrepreneurship to Face Global Challenges - Lukito, Daniel (PT. Riset Press International, 2024)
This research aims to highlight the value of entrepreneurial leadership in developing students' leadership capabilities. By using various leadership styles, this research attempts to provide insights into how entrepreneurial leadership can be applied in higher education to improve the human resources, industry, and education sectors. Various leadership philosophies have been applied in entrepreneurial endeavors over the past few years, but more research is needed to identify the most effective leadership styles, especially for university students. The results of this study suggest that different entrepreneurial leadership approaches and leadership philosophies among university students may contribute to the development of characters who are creative, well-behaved, and possess important leadership qualities.